The Persistence of Habit: Tantric Engagements with Dharmakīrti’s View of Yogic Perception - Davey K. Tomlinson (Journal of Contemplative Studies)
Dharmakīrti’s view of yogic perception (yogipratyakṣa) and mental cultivation (bhāvanā) has generated a good deal of discussion—in Dharmakīrti’s text tradition, in the works of its various critics, and in the contemporary study of Buddhist philosophy. It is discussed not infrequently in Buddhist tantric works, too. However, tantric authors’ appeals to yogic perception are at odds with Dharmakīrti’s intentions in important ways. In this paper, I show why this appropriation of Dharmakīrti on yogic perception might be surprising, and then I reveal a tantalizing thread of Dharmakīrtian thinking about cultivation that nevertheless runs through certain Sanskrit Buddhist tantric debates. What is most crucial about Dharmakīrti for these authors, I argue, is his reasoned defense of cultivation’s power: its capacity to fundamentally and irreversibly transform the practitioner’s cognitive, conative, and experiential habits. I develop this point with reference especially to a tantric treatise attributed to Śāntarakṣita, The Accomplishment of Reality (Tattvasiddhi).